Aversive eye gaze during a speech in virtual environment in patients with social anxiety disorder. (March 2018) - Kim, Haena; Shin, Jung Eun; Hong, Yeon-Ju; Shin, Yu-Bin; Shin, Young Seok; Han, Kiwan; Kim, Jae-Jin; Choi, Soo-Hee
Objective: One of the main characteristics of social anxiety disorder is excessive fear of social evaluation. In such situations, anxiety can influence gaze behaviour. Thus, the current study adopted virtual reality to examine eye gaze pattern of social anxiety disorder patients while presenting different types of speeches. Methods: A total of 79 social anxiety disorder patients and 51 healthy controls presented prepared speeches on general topics and impromptu speeches on self-related topics to a virtual audience while their eye gaze was recorded. Their presentation performance was also evaluated. Results: Overall, social anxiety disorder patients showed less eye gaze towards the audience than healthy controls. Types of speech did not influence social anxiety disorder patients' gaze allocation towards the audience. However, patients with social anxiety disorder showed significant correlations between the amount of eye gaze towards the audience while presenting self-related speeches and social anxiety cognitions. Conclusion: The current study confirms that eye gaze behaviour of social anxiety disorder patients is aversive and that their anxiety symptoms are more dependent on the nature of topic.